PREVALENCE OF LEPTOSPIRA SP. IN TWO CATTLE FARMS OF PUNO - Cachata R., Susana (2008)
The prevalence of bovine leptospirosis in 103 cattle (98 female and 5 male) from two farms of the Puno province were studied. Blood samples were collected during February and March 2005 (rainy season), and sera was confronted with four serovar reference of Leptospira interrogans by the Microscopic Agglutination Test (MAT). Two positive samples with titres of 1:100 and 1:200 were detected, representing a prevalence of 2.9%. The involved serovar was Leptospira icterohaemorrhagiae.